Catalytic conversion of triglycerides by metal-based catalysts and subsequent modification of molecular structure by ZSM-5 and Raney Ni for the production of high-value biofuel. (September 2020) - Long, Feng; Zhai, Qiaolong; Liu, Peng; Cao, Xincheng; Jiang, Xia; Wang, Fei; Wei, Linshan; Liu, Chao; Jiang, Jianchun; Xu, Junming
Abstract: We report herein a catalytic deoxygenation strategy that allows the direct removal of oxygen atoms from triglycerides by lowering the activation energy through the use of metal-based catalysts. Activation energies were investigated by TG analysis, employing fatty acid salts as model compounds. Introducing different metal atoms into carboxyl groups has a substantial effect on the dynamic pyrolytic behavior, and decomposition activation energies varied in the range 80–260 kJ/mol. The catalytic cracking of soybean oil using SnO as a representative catalyst has been investigated in a 5 L reactor, whereby the catalyst lowered the decomposition temperature by approximately 40 °C and gave a conversion rate of approximately 66 wt%. A catalytic conversion mechanism has been proposed based on the results of TG-FTIR, GC, and GC-MS analyses. The pyrolysis products from the deoxygenation process had a high alkene content, endowing them with great potential for conversion into cyclic hydrocarbons used in real aviation fuels. Such conversion through aromatization and hydrogenation over ZSM-5 and Raney Ni catalyst has been investigated. Overall, a new refining process, including conversion of triglycerides to alkanes and terminal alkenes catalyzed by metal compounds, furnishing viable aviation and diesel fuels, is reported. Graphical abstract: Image 1 Highlights: Catalytic conversion of triglycerides to product hydrocarbons without hydrogen consumption. Dynamic behavior has been investigated through TG analysis for selecting cracking catalyst. Deoxygenation strategies were investigated and catalytic conversion mechanism was proposed. Pyrolysis oil was aromatized and hydrogenated can production aviation biofuel and biodiesel.